Time to resolution of tubal ectopic pregnancy following methotrexate treatment: A retrospective cohort study - Davenport, Marcus J.; Lindquist, Anthea; Brownfoot, Fiona; Pritchard, Natasha; Tong, Stephen; Hastie, Roxanne (PLOS ONE, 2022)
Objective To determine the time to resolution of tubal ectopic pregnancy after methotrexate treatment. Methods A 14-year retrospective cohort study was performed from 2004–2018 and assessed 216 women treated with single-dose methotrexate for tubal ectopic pregnancy. Women were treated using a single-dose protocol of intramuscular methotrexate (50mg/m2) for confirmed tubal ectopic pregnancy on ultrasound. Ectopic pregnancies were included if the ectopic pregnancy mass was <35mm, no evidence of rupture and no embryonic cardiac activity. Serum hCG was measured on day 1, 4 and 7 of treatment and then at standard weekly intervals until resolution. Where there was not a ≥15% decline in hCG from day 4 and day 7, a second dose of methotrexate was administered. The primary outcome was time to resolution (days), with serum hCG <5 IU/L considered resolved. The secondary outcome was need for rescue surgery. Results Among women who did not proceed to surgery, the median time to resolution was 22 days (IQR 14,34). Time to resolution and need for rescue surgery increased with baseline hCG. When hCG was <1000 IU/L, the median was 20 days (IQR 13,29) but 34.5 days (IQR 22,48) with hCG >2000 IU/L. Early hCG trends were predictive of time to resolution and likelihood of rescue surgery; a hCG rise of >1000 IU/L between Days 1–4 increased time to resolution to 61 days (IQR 35,80) and an odds ratio of rescue surgery of 28.6 (95% C.I. 5.3,155.4). Conclusion The median time to resolution for ectopic pregnancies treated with methotrexate is 22 days and associated with baseline hCG levels. The predictive value of baseline hCG may be useful in clinical decision making and counselling women considering methotrexate for ectopic pregnancy.